Identification of Genes Involved in Indole-3-Acetic Acid Biosynthesis by Gluconacetobacter diazotrophicus PAL5 Strain Using Transposon Mutagenesis - Rodrigues, Elisete P.; Soares, Cleiton de Paula; Galvão, Patrícia G.; Imada, Eddie L.; Simões-Araújo, Jean L.; Rouws, Luc F. M.; Oliveira, André L. M. de; Vidal, Márcia S.; Baldani, José I. (Frontiers in Microbiology, 2016)
Gluconacetobacter diazotrophicus is a beneficial nitrogen-fixing endophyte found in association with sugarcane plants and other important crops. Beneficial effects of G. diazotrophicus on sugarcane growth and productivity have been attributed to biological nitrogen fixation process and production of phytohormones especially indole-3-acetic acid (IAA); however, information about the biosynthesis and function of IAA in G. diazotrophicus is still scarce. Therefore, the aim of this work was to identify genes and pathways involved in IAA biosynthesis in this bacterium. In our study, the screening of two independent Tn5 mutant libraries of PAL5T strain using the Salkowski colorimetric assay revealed two mutants (Gdiaa34 and Gdiaa01), which exhibited 95% less indolic compounds that the parental strain when grown in LGIP medium supplemented with L-tryptophan. HPLC chromatograms of the wild-type strain revealed the presence of IAA and of the biosynthetic intermediates indole-3-pyruvic acid (IPyA) and indole-3-lactate (ILA). In contrast, the HPLC profiles of both mutants showed no IAA but only a large peak of non-metabolized tryptophan and low levels of IPyA and ILA were detected. Molecular characterization revealed that Gdiaa01 and Gdiaa34 mutants had unique Tn5 insertions at different sites within the GDI2456 open read frame, which is predicted to encode a L-amino acid oxidase (LAAO). GDI2456 (lao gene) forms a cluster with GDI2455 and GDI2454 ORFs, which are predicted to encode a cytochrome C and an RidA protein, respectively. RT-qPCR showed that transcript levels of lao, cccA and ridA genes were reduced in the Gdiaa01 as compared to PAL5T. In addition, rice plants inoculated with Gdiaa01 showed significantly smaller root development (length, surface area, number of forks and tips) than those plants inoculated with PAL5T. In conclusion, our study demonstrated that G. diazotrophicus PAL5T produces IAA via the IPyA pathway in cultures supplemented with tryptophan and provides evidence for the involvement of an L-amino acid oxidase gene cluster in the biosynthesis of IAA. Furthermore, we showed that the mutant strains with reduction in IAA biosynthesis ability, in consequence of the lower transcription levels of genes of the lao cluster, had remarkable effects in development of rice roots.